2005
DOI: 10.1099/jmm.0.46160-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simple detection of bla CTX−M genes by multiplex PCR assay

Abstract: A novel multiplex PCR assay is described (CTX-Mplex PCR) that allows rapid detection of bla CTX-M genes and discrimination between groups 1, 2, 9 and 25/26. The specificity and sensitivity of the assay were evaluated with 10 control strains and then applied to 62 clinical isolates. The multiplex PCR detected and classified bla CTX-M genes with 100 % accuracy. The utilization of a denaturing HPLC WAVE system to size the PCR products automatically from the multiplex PCR enhances the assay by saving time and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 27 publications
1
73
2
1
Order By: Relevance
“…Also, other studies showed the dissemination of CTX-M8 gene in Iran are higher than other parts of the world (34) On the other hand, in this study, the frequency of CTX-M-9 in isolates was less than Germany, America, Canada (ranged 38.5%-58.5%) (35,36).…”
Section: Discussioncontrasting
confidence: 42%
“…Also, other studies showed the dissemination of CTX-M8 gene in Iran are higher than other parts of the world (34) On the other hand, in this study, the frequency of CTX-M-9 in isolates was less than Germany, America, Canada (ranged 38.5%-58.5%) (35,36).…”
Section: Discussioncontrasting
confidence: 42%
“…All of the Salmonella isolates were screened by PCR for transferable PMQR-encoding genes, including qnrA, qnrB, qnrC, qnrD, qnrS, oqxAB, aac-(6=)-Ib, and qepA, as previously described (11,12). A multiplex PCR was used to screen for bla CTX-M in all of the ESBL-producing isolates (23). Another multiplex PCR method was applied to screen for plasmid-mediated AmpC-encoding genes in clavulanic acid-resistant isolates (24).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of β-lactamase genes: β-Lactamase genes were detected by PCR and direct DNA sequencing according to a method described in previous studies [17,25,38].…”
Section: Methodsmentioning
confidence: 99%